Introduction to the Frontiers Research Topic: Optimization of Exercise Countermeasures for Human Space Flight – Lessons From Terrestrial Physiology and Operational Considerations - Scott, Jonathan P. R.; Weber, Tobias; Green, David A. (Frontiers in Physiology, 2019)
Exercise in space has evolved from rudimental testing into the multi-modal countermeasure (CM) programme used on the International Space Station (ISS). However, with the constraints of future exploration missions, replicating this programme will be a significant challenge. Recent ISS data suggest that crew now experience only relatively moderate levels of microgravity (G)-induced adaptation, although significant variation remains, with some crew displaying marked changes despite significant time/effort investment. This suggests that the efficacy of exercise CMs is yet to be optimised for all individuals. With the current suite of exercise devices operational for almost a decade, and with exploration approaching, it is timely to re-visit the terrestrial literature to identify new knowledge relevant to the management of µG adaptation. As such, the aim of the Frontiers Research Topic Optimisation of Exercise Countermeasures for Human Space Flight – Lessons from Terrestrial Physiology and Operational Considerations, is to synthesize current terrestrial exercise physiology knowledge and consider how this might be employed to optimise the use of exercise CM. The purpose of this Perspective, which serves as a preface to the Research Topic is three-fold: to briefly review the use and apparent efficacy of exercise in space, to consider the impact of the transition from ISS to exploration mission vehicles and habitats and to identify areas of terrestrial exercise physiology where current knowledge might contribute to the optimisation of CM exercise for exploration. These areas include individual variation, high intensity interval training, strength development/maintenance, concurrent training, plyometric/impact exercise and strategies to enhance exercise efficacy.